Pengaruh Karakteristik Auditor terhadap Kualitas Audit - Lintang Kurniawati; Nur Kholis; Hestin Mutmainah (Journal of Applied Accounting and Taxation, 2019)
The purpose of this study is to examine the effect of auditor characteristics (competence, independence and accountability) on audit quality. Respondents from this study were auditors of the public accountant office in Surakarta consisting of 45 respondents, the research method used in this study was purposive sampling and tested using multiple linear regression. The results of this study indicate that competence and accountability influence audit quality, this shows that the more competent an auditor and auditor who has good accountability will affect the quality of the audited, while Independence does not affect audit quality.